The flipped classroom model for an undergraduate epidemiology course - Sangho Sohn; Young-Mee Lee; Jaehun Jung; Eun Shil Cha; Byung Chul Chun (Korean Journal of Medical Education, 2019)
Purpose The flipped classroom has been suggested as a method for efficient teaching in medical education. However, its feasibility and effectiveness in the educational environment are often overlooked. The authors redesigned an epidemiology course applying the flipped classroom method under a traditional curriculum consisting of heavily scheduled classroom hours and explored its feasibility and effectiveness. Methods In the fall semester of 2017, we flipped the ‘practice of epidemiology’ course for third-year medical students at Korea University College of Medicine. We provided online lectures and assigned readings as pre-class materials, and substituted group discussions and communicative activities for traditional lectures. We conducted pre- and post-course surveys to review students’ perceptions. We also analyzed the pre-test results and final exam scores for quantitative comparison. Results Ninety-seven students out of 120 completed the course. Most students made use of the online lectures, but not the reading materials. Lack of time was the most frequently cited reason for under-preparedness. We observed improvements in preparedness, participation, and effectiveness at the end of the course, while changes in satisfaction were unclear. Students’ perceptions of course relevance and difficulty were predictive of pre-test outcomes, but the effects of preparedness and length of materials were insignificant. The authors found no evidence of differing test scores before and after the course. Conclusion This study supports the feasibility of the flipped classroom model even under a traditional, heavily scheduled medical curriculum. To encourage self-directed learning and achieve better learning outcomes, restructuring pre-existing curricular components should also be considered in parallel with new instructional methods.